The Use of Language Variation on the Social Media Twitter: - Nisa Rahmadiana; Yeni Rahmawati; Farah Nazifa; Fuan Fazrayana; Hidayatur Rahmi; Daini Rizki; Istiqamah (Raja Zulkarnain Education Foundation, 2026)
Language variation is the variety of language used by society. Talking about language variation, it cannot be separated from the aspect of communication, both verbally and in writing. In this study, researchers will examine the use of language variation from the perspective of speakers on social media Twitter. Types of language variation from the perspective of speakers are divided into four, one of which is sociolect. Sociolect is further divided into eight, namely acrolect, basilect, vulgar, slang, colloquial, jargon, argot, and ken. Acrolect is a type of language variation that has a higher status. Basilect is a type of language variation that is considered to have a lower status or the opposite of acrolect. Vulgar is a type of language variation that contains rude or dirty words. Slang is a type of language variation that is specific and commonly used by teenagers and often changes. Colloquial is a type of spoken language variation that is commonly used daily. Jargon is a type of language variation that is limited in nature and is used only in certain groups or fields but is not closed. Argot is a type of language variation that is used in certain fields and is secretive, the opposite of jargon. Ken is a type of language variation used to request or influence and is full of falsehood. The purpose of this study is to analyze sociolect language variations based on the speaker’s perspective on Twitter social media, including posts, tweets, comments, and others. The research method used was qualitative to produce descriptive data, namely data that is in accordance with the results of the analysis. The data found a total of 20 data. There are 2 data for the type of acrolect, 3 data for the type of basilek, 6 data for vulgarity, 3 data for slang, 1 data for colloquial, 2 data for jargon, 2 data for argot and 1 data for ken. Thus, it can be concluded that there are many variations of language used on Twitter social media, both from teenagers and adults to the elderly, which are very diverse.